2012
DOI: 10.1017/s096354831100068x
|View full text |Cite
|
Sign up to set email alerts
|

The Size of a Hypergraph and its Matching Number

Abstract: More than forty years ago, Erdős conjectured that for any t ≤ n k , every k-uniform hypergraph on n vertices without t disjoint edges has at most maxedges. Although this appears to be a basic instance of the hypergraph Turán problem (with a t-edge matching as the excluded hypergraph), progress on this question has remained elusive. In this paper, we verify this conjecture for all t < n 3k 2 . This improves upon the best previously known range t = O n k 3 , which dates back to the 1970's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 9 publications
7
103
0
Order By: Relevance
“…Bollobás, Daykin and Erdős [4] proved Conjecture 1.1 for general k whenever s < n/(2k 3 ), which extended earlier results of Erdős [8]. Huang, Loh and Sudakov [14] proved it for s < n/(3k 2 ). The main result in this paper verifies Conjecture 1.1 asymptotically for matchings of any size up to almost half the size of a perfect matching.…”
Section: Large Matchings In Hypergraphs With Many Edgessupporting
confidence: 72%
See 1 more Smart Citation
“…Bollobás, Daykin and Erdős [4] proved Conjecture 1.1 for general k whenever s < n/(2k 3 ), which extended earlier results of Erdős [8]. Huang, Loh and Sudakov [14] proved it for s < n/(3k 2 ). The main result in this paper verifies Conjecture 1.1 asymptotically for matchings of any size up to almost half the size of a perfect matching.…”
Section: Large Matchings In Hypergraphs With Many Edgessupporting
confidence: 72%
“…The main result in this paper verifies Conjecture 1.1 asymptotically for matchings of any size up to almost half the size of a perfect matching. This gives an asymptotic answer to a question in [14]. Theorem 1.2.…”
Section: Large Matchings In Hypergraphs With Many Edgesmentioning
confidence: 83%
“…For k = 2 (graphs) the value of n 0 (2, t) was determined by Erdős and Gallai [2]. The case k = 3 was recently investigated by Frankl, Rödl, and Rucinśki [10] and n 0 (3, t) was finally determined by Luczak and Mieczkowska [21] for large t, and by Frankl [6] for all t. In general, Huang, Loh, and Sudakov [16] showed n 0 (k, t) < 3tk 2 , which was slightly improved in [9] and greatly improved to n 0 (k, t) ≤ (2t + 1)k − t by Frankl [7]. Frankl [5] showed that for every n, k, t if a k-graph F on [n] has no t + 1 pairwise disjoint edges then |F| ≤ t n−1 k−1 .…”
Section: Given Setsmentioning
confidence: 99%
“…Hypergraphs model more general types of relations than graphs. For more results on hypergraph, we refer to [1,2,5,[11][12][13]. The matching polynomial of a graph was introduced by Farrell in 1979.…”
Section: Introductionmentioning
confidence: 99%